EFFECTIVENESS OF ERGOTHERAPEUTIC AND OCCUPATIONAL THERAPEUTIC PROGRAM IMPLEMENTED FOR CHILDREN AND YOUTHS WITH DISABILITIES IN FAMILY-TYPE RESIDENTIAL CENTERS - Danelina Vacheva; Iskra Petkova (Peytchinski Publishing, 2021)
The purpose of this study is to report the effectiveness of ergotherapy and occupational therapy activities included in upbringing and education of children and youths with disabilities that use the social service "Family-type accommodation center". Materials and Methods: The study included 37 users using the relevant social service in the Municipality of Pleven, distributed by age groups and degree of disability. A survey was conducted with 26 employees in these Centers to determine the impact of the program on consumer development. Tests were performed to assess the skills for independent daily life. The obtained results were processed statistically to determine their significance. Results: The data from the study show a statistically significant positive impact of the selected ergo- and occupational therapy program in children and young people with disabilities raised in Family-type Centers, and is most significant in children of preschool and primary school age. The improvement in young people with severe physical and mental disabilities is expected to be insignificant, but the results of the survey of employees show a positive effect on their psycho-emotional state. Conclusion: Inclusion of an appropriate ergo- and occupational therapy program in the upbringing and education of children and young people with disabilities, who are in a disadvantaged social position and use social services, has a favorable impact on the formation of their skills for independent living.